Carbon Default Swap - Disentangling the Exposure to Carbon Risk through CDS - Alexander Blasberg; Rüdiger Kiesel; Luca Taschini (Center for Economic Studies and ifo Institute (CESifo), 2022)
Using Credit Default Swap spreads, we construct a forward-looking, market-implied carbon risk factor and show that carbon risk affects firms' credit spread. The effect is larger for European than North American firms and varies substantially across industries, suggesting the market recognises where and which sectors are better positioned for a transition to a low-carbon economy. Moreover, lenders demand more credit protection for those borrowers perceived to be more exposed to carbon risk when market-wide concern about climate change risk is elevated. Finally, lenders expect that adjustments in carbon regulations in Europe will cause relatively larger policy-related costs in the near future.
Keywords: C21; C23; G12; G32; Q54; 330; climate change; carbon risk; credit risk; Credit Default Swap spreads